Investigation of DNA-Binding Ability Between Di(p-aminobenzoato)tetraaquacobalt(II) Complex and Cat Genomic DNA - Arslantas, Ali; Kadir Devrim, A.; Szmen, Mahmut; Necefoglu, Hacali (Asian Journal of Chemistry, 2010)
The di(p-aminobenzoato)tetraaquacobalt(II) complex [Co(PAB), where PAB is p-NH2C6H5CO2, has been obtained by the condensation of p-aminobenzoate in the presence of cobalt(II) sulfate. The interaction of complex of Co(PAB) with the cat genomic DNA was investigated by spectroscopic, gel electrophoresis, fluoresence spectroscopy and viscosity measurements. The experimental data indicate that the complex may bind to DNA via an intercalative manner. The viscosity measurements and electrophoresis with spectroscopic studies support that complex, interacting with the cat genomic DNA by an intercalation mode through the base pairs of DNA.